The Bank Lending Channel and the Market for Banks' Wholesale Funding - Maximilian Breitenlechner; Johann Scharler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The bank lending channel (BLC) holds that monetary policy is transmitted through the supply of bank loans. While the original formulation of the BLC stresses an imperfect substitution between reservable and non-reservable sources of banks' funding, as the transmission mechanism, recent contributions highlight changes of banks' risk premia as a more relevant link between monetary policy and loan supply. Using U.S. data, we quantify the relative importance of these two complementary channels with a SVAR approach. The differently transmitted monetary policy shocks are identified with sigh restrictions that disentangle different dynamics on the market for banks' wholesale funding. We find that policy shocks associated with dynamics on the wholesale funding market that are consistent with the traditional BLC or changes in banks' risk premia, contribute both to the variation of total loans, with the latter mechanism being nearly twice as strong as the traditional BLC.
Keywords: E44; E52; C32; 330